2023
DOI: 10.3390/ijms24054315
|View full text |Cite
|
Sign up to set email alerts
|

Glucokinase Inactivation Ameliorates Lipid Accumulation and Exerts Favorable Effects on Lipid Metabolism in Hepatocytes

Abstract: Glucokinase-maturity onset diabetes of the young (GCK-MODY) is a kind of rare diabetes with low incidence of vascular complications caused by GCK gene inactivation. This study aimed to investigate the effects of GCK inactivation on hepatic lipid metabolism and inflammation, providing evidence for the cardioprotective mechanism in GCK-MODY. We enrolled GCK-MODY, type 1 and 2 diabetes patients to analyze their lipid profiles, and found that GCK-MODY individuals exhibited cardioprotective lipid profile with lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Mazier et al [15] found that C. minuta DSM33407 suppressed hepatic lipid accumulation in high-fat diet-fed animals in association with strong repression of the Glucokinase (Gck) gene. Gck inhibition ameliorates hepatic lipid accumulation and inflammation by altering the expression of genes involved in adipogenesis, lipolysis and β-oxidation in the liver [78] . Claudin-1 (Cldn1), Occludin (Ocln), Zonula Occludens-1 (Zo1) is required for the maintenance of a functional intestinal barrier [79] .…”
Section: Metabolic Regulationmentioning
confidence: 99%
“…Mazier et al [15] found that C. minuta DSM33407 suppressed hepatic lipid accumulation in high-fat diet-fed animals in association with strong repression of the Glucokinase (Gck) gene. Gck inhibition ameliorates hepatic lipid accumulation and inflammation by altering the expression of genes involved in adipogenesis, lipolysis and β-oxidation in the liver [78] . Claudin-1 (Cldn1), Occludin (Ocln), Zonula Occludens-1 (Zo1) is required for the maintenance of a functional intestinal barrier [79] .…”
Section: Metabolic Regulationmentioning
confidence: 99%
“…Given the adverse consequences of over-activation of hepatic GK, some researchers have proposed that inhibiting hepatic GK may have potential metabolic benefits ( 146 , 147 ). However, more important is how to strike a balance between the activation and inhibition.…”
Section: Novel Strategies For Targeting Gk or Gkrp For The Treatment ...mentioning
confidence: 99%
“…To investigate the link between differential DNA methylation and non-B DNA formation in MetDs, we performed locus-specific 5mC analysis in the gene body of two key metabolic genes, exon 7 of glucokinase (GCK) and the intron 2-exon 3 boundary of transmembrane 6 superfamily 2 (TM6SF2) using 148 blood samples from a well-characterized cohort including lean and obese healthy subjects, lean and obese MAFLD, and patients suffering from advanced MetDs including uncontrolled T2DM and severe MAFLD, collected at the University Hospital Salzburg, Austria. GCK and TM6SF2 are not only known risk genes (GCK (40)(41)(42)(43), TM6SF2 (44)(45)(46)(47)(48)), but are also targets for drug design (49). In this study, we focused on intragenic regions overlapped by long non-coding RNAs, which potentially form R-loops in these genes and enhance G4 formation.…”
Section: Introductionmentioning
confidence: 99%